Color in Mental Maps and Geoconcepts of China - Konstantin I. Belousov; Jingzhi Duan; Natalia L. Zelianskaia (Виртуальная коммуникация и социальные сети)
This paper is devoted to the study of the role of color in the objectification of mental representations of geographic space in the mental map form. It also examines the influence of color tradition associated with a geo-object on the structural-semantic organization of its geoconcept. The relevance of this research is due, on the one hand, to the contemporary cognitive scientific interest in mental space representations, and, on the other, to the investigation of the functions of sensory information in the organization and objectification of these representations. The research methodology involves a multi-stage process, including: (a) the collection of digital mental maps, carried out with the web application "Creative Map Studio"; (b) the preprocessing analysis and visualization of respondents’ color associations using Python and its libraries; (c) the semantic analysis of the textual layer of mental maps and the construction of graph-semantic models of geoconcepts. The study is based on 247 mental maps of China collected in 2019–2024 in Chinese universities. With the new empirical material, the paper statistically confirms the structure-forming functions of color in the organization of geo-mental representations of space, revealing a statistically significant relationship between the number of used color shades and the volume structural information in the mental maps. In addition, the study supports the hypothesis that color has a natural clustering function in the structural-semantic organization of geoconcepts (as exemplified by the geoconcept of Shanghai).